The use of connectives in the written production in Croatian as a mother tongue and English and German as foreign languages - Pon, Leonard (Poznańskie Studia Slawistyczne, 2025)
The ability to write texts is an important aspect of foreign language learning, which includes producing a coherent and well-structured text. One of the ways to achieve that is the explicit marking of the relationship between the propositions in a text through the appropriate use of connectives. The aim of this paper is to discover similarities and differences between Croatian as a mother tongue and English and German as foreign languages regarding the use of connectives. The corpus for the study consists of 32 argumentative essays in each of the three languages. The study is based on the analysis of connectives with regard to their frequency, meaning, as well as the appropriateness and the correctness of their use. The analysis revealed a greater range of connectives in Croatian, differences in their patterns of use across languages, instances of their incorrect use in both foreign languages, and similarities across all three languages regarding their appropriateness of use.